ORAL HEALTH STATUS IN PATIENTS WITH RHEUMATOID ARTHRITIS - Yusubova, Sh.R.; Seyidova, I.Z.; Bayramov, G.R. (World of Medicine and Biology, 2025)
To investigate the prevalence and structure of dental disease among patients with rheumatoid arthritis in Azerbaijan, 123 patients with rheumatoid arthritis underwent dental examinations. The control group consisted of 130 individuals without any somatic diseases. The oral hygiene status was assessed using the Greene-Vermillion Hygiene Index. The periodontal status was evaluated using the Mühlemann Bleeding Index, Svarkova Iodine Test, Gingival Index, and the Fuchs and Ramfjord indices. Periodontitis was identified in 63.4 % of RA patients, markedly higher than in the control group, where it was observed in only 33.9 %. The findings revealed significant differences between the two cohorts across several oral health indicators (Svarkova Iodine, the Fuchs and Ramfjord indices). These results indicate that patients with rheumatoid arthritis exhibit a higher prevalence of several stomatological conditions (particularly periodontitis, gingivitis, pulpitis, and mucosal diseases) compared to individuals without somatic diseases.